Correlation between HbA1c levels and intrastent restenosis incidence in patients with diabetes mellitus after percutaneous coronary intervention at Dr. Saiful Anwar General Hospital - Millisani, Hayla Iqda; Prasetya, Indra; Rohman, Mohammad Saifur (Heart Science Journal, 2024)
Background: Patients with chronic uncontrolled diabetes mellitus as indicated by HbA1c levels â‰¥ 6.5%, increase the risk of atherosclerosis, thereby increasing in-stent restenosis incidence during and after percutenous coronary intervention. Regular monitoring of HbA1c is crucial to reduce the incidence of in-stent restenosis.Objective: This study aims to ascertain the correlation between HbA1c levels and in-stent restenosis incidence in diabetes mellitus patients after percutenous coronary intervention at Dr. Saiful Anwar General Hospital, Malang, East Java, Indonesia.Methods/Design: Analytical observational study with a retrospective cohort study approach to determine the correlation between HbA1c levels and the incidence of in-stent restenosis in patients with diabetes mellitus after percutenous coronary intervention. The research sample was carried out by consecutive sampling in January 2021-December 2023.Results: This study has recruited 555 patients with coronary artery disease and diabetes mellitus. The average age of coronary heart disease patients with diabetes mellitus was 59 years. Patients with HbA1c levels â‰¥6.5 were more prone to experience in-stent restenosis 54 patients, while those with HbA1c levels <6.5 were more prone not to experience in-stent restenosis 388 patients, indicating a significant correlation between HbA1c and in-stent restenosis p=0.024. in-stent restenosis was most frequently observed in the LAD 44 patients, RCA 13 patients, LCx 10 patients, and LM 0 patient. The highest percentage of in-stent restenosis cases was over 70%, with 3VD lesions being the most common 55 patients. OAD therapy is most often given to coronary heart disease patients with diabetes mellitusConclusion: There is a correlation between HbA1c levels and the incidence of in-stent restenosis in diabetes mellitus patients after percutaneous coronary intervention, underscoring the necessity for routine blood glucose monitoring to prevent in-stent restenosis.